Aplikasi Sistem Pakar untuk Diagnosa Penyakit pada Padi dengan Metode Forward Chaining - Selly Nur Holifah; Apriliyan Mahardika S.; Rizky Tiwa Saputra; Umul Musfiroh Nurali; Aries Saifudin; Endar Nirmala (Jurnal Informatika Universitas Pamulang, 2021)
The development of information systems, more and more systems are needed that support in all fields, for example in the agricultural environment. One of the many information systems needed in agriculture is an expert system that can diagnose diseases in rice. Because there are still many people who still lack knowledge about the symptoms and diseases that can attack rice. So an application is made using the forward chaining method that can diagnose diseases in rice which can make it easier for the public to know the diseases that attack rice so they can immediately find solutions and reduce factors that can cause a decrease in the amount of rice staples for the wider community.